2014
DOI: 10.1007/5584_2014_32
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Consumption Pattern in the Neonatal Special Care Unit Before and After Implementation of the Hospital’s Antibiotic Policy

Abstract: Current and detailed knowledge of antibiotic use is essential in order to implement strategies for reducing the overuse of antibiotics. The objective of our study was to determine the effectiveness of the implementation of the hospital antibiotic policy (HAP) by assessing antibiotic consumption in the Special Neonatal Care Unit (SNCU) in Warsaw, Poland, before and after this intervention. Antibiotic use was calculated in daily defined doses (DDDs) per 100 patient-days and DDDs per 100 admissions. The antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
(26 reference statements)
1
13
0
Order By: Relevance
“…Studies conducted in the United States (30,(34)(35)(36) and in Europe (29,33,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) reported the highest pooled decrease in antimicrobial consumption after the implementation of ASP (Ϫ19.9% [95% CI ϭ Ϫ27.7 to Ϫ12.1, 2 ϭ 0.00] and Ϫ20.9% [95% CI ϭ Ϫ30.5 to Ϫ15, 2 ϭ 0.05], respectively), whereas studies in Asia reported a reduction of Ϫ16% (95% CI ϭ Ϫ36.5 to Ϫ5.3], 2 ϭ 0.11) (28, 31, 32, 47-52) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in the United States (30,(34)(35)(36) and in Europe (29,33,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) reported the highest pooled decrease in antimicrobial consumption after the implementation of ASP (Ϫ19.9% [95% CI ϭ Ϫ27.7 to Ϫ12.1, 2 ϭ 0.00] and Ϫ20.9% [95% CI ϭ Ϫ30.5 to Ϫ15, 2 ϭ 0.05], respectively), whereas studies in Asia reported a reduction of Ϫ16% (95% CI ϭ Ϫ36.5 to Ϫ5.3], 2 ϭ 0.11) (28, 31, 32, 47-52) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 shows that the ATC/DDD system was only used in three studies evaluating antibiotics (Liem et al, 2010b ; Porta et al, 2012 ; Nitsch-Osuch et al, 2013 ). Two studies used the DDD system without ATC classification, whereas one study reported antibiotics consumption using Days of Therapy (Zingg et al, 2011 ; Salehifar et al, 2014 ; Nitsch-Osuch et al, 2015 ). Only one study reported antibiotics consumption using the PDD system (Porta et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study reported antibiotics consumption using the PDD system (Porta et al, 2012 ). In addition, DU90 or DU100% was used as one of the reporting methods in four studies evaluating antibiotic utilization (Liem et al, 2010b ; Porta et al, 2012 ; Nitsch-Osuch et al, 2013 , 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…These results are thus more advantageous than those described previously for the Special Care Neonatal Unit (SCNU) (Nitsch-Osuch et al 2015), where just the consumption pattern of antibiotics was improved. The difference may be explained by several factors.…”
Section: Discussionmentioning
confidence: 72%